Winner-Loser Reversals in National Stock Market Indices : Can they Be Explained? - Richards, Anthony (IMF Working Papers; Working Paper ;, 1997)
This paper examines possible explanations for 'winner-loser reversals' in the national stock market indices of 16 countries. There is no evidence that loser countries are riskier than winner countries either in terms of standard deviations, covariance with the world market or other risk factors, or performance in adverse economic states of the world. While there is evidence that small markets are subject to larger reversals than large markets, perhaps because of some form of market imperfection, the reversals are not just a small-market phenomenon. The apparent anomaly of winner-loser reversals in national market indices therefore remains unresolved.